2019
DOI: 10.1021/acs.cgd.9b00856
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Composition Gradient on Microdomain Structure and the Macro-Ferroelectric/Piezoelectric Properties

Abstract: Internal fields caused by strain gradient, composition gradient (CG), and space charges have significant influences on micro and macro properties of ferroelectrics. Here, we report the relationship among composition gradient, microdomain structure, and macroscopic ferroelectric/piezoelectric properties. Three KTa1–x Nb x O3 samples with the same Curie temperature T c = 39 °C and different CGs are designed and investigated. As CG decreases, the scale of domains decreases from ∼10 μm to 200 nm, and the spontaneo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
0

Year Published

2019
2019
2025
2025

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 42 publications
(71 reference statements)
0
11
0
Order By: Relevance
“…The DC electric-field-induced P C−T also can be distinguished by this way, because ferroelectric domain is a typical feature of the ferroelectric phase for KTN crystals. Such domain (90°d omain) structures, to minimize the free energy associated with polarization charge, 41 can be attributed to the great grain size of a sample; 42 and these domain structures are also observed in the process of temperature-induced phase transition, which was measured by Huang et al 43 In addition, the E−T phase diagram (as shown in Figure 6b) is obtained from Figure 6a. The E−T phase diagram shows the close to linear variation of phase transition electric field with the temperature in the whole measured temperature range and the expression of the linear variation is E = 0.6T − 185.2, which is consistent with the result obtained by Khemakhem et al 44 And we see that because of the linear variation, the critical electric field of P C−T shifts to higher value as temperature increases.…”
Section: Methodsmentioning
confidence: 75%
“…The DC electric-field-induced P C−T also can be distinguished by this way, because ferroelectric domain is a typical feature of the ferroelectric phase for KTN crystals. Such domain (90°d omain) structures, to minimize the free energy associated with polarization charge, 41 can be attributed to the great grain size of a sample; 42 and these domain structures are also observed in the process of temperature-induced phase transition, which was measured by Huang et al 43 In addition, the E−T phase diagram (as shown in Figure 6b) is obtained from Figure 6a. The E−T phase diagram shows the close to linear variation of phase transition electric field with the temperature in the whole measured temperature range and the expression of the linear variation is E = 0.6T − 185.2, which is consistent with the result obtained by Khemakhem et al 44 And we see that because of the linear variation, the critical electric field of P C−T shifts to higher value as temperature increases.…”
Section: Methodsmentioning
confidence: 75%
“…Under low frequency, KTN displays a normal P-E loop with an apparent remanent polarization value. [23,24] The origin of double-loop hysteresis should be more possibly attributed to the recoverable reorientation of the asymmetric polar domains induced by the component gradient of Ta/Nb. To understand the relationship between ferroelectric order and photoelectric response, we fabricated KTN-based photodetectors with cubic KTN1 and tetragonal KTN2, KTN3, and KTN4 crystals.…”
Section: Resultsmentioning
confidence: 99%
“…Potassium tantalum niobate (KTa 1– x Nb x O 3 , KTN) single crystals possess excellent optical and ferroelectric properties. As a first-order phase transition (FPT) ferroelectric, KTN has been proven to exhibit an EC performance. , For example, KTN modified with Li + gave rise to a large EC property of Δ T ∼ 0.42 K (under 20 kV cm –1 ).…”
Section: Introductionmentioning
confidence: 99%